Islamophobia, Clash of Civilizations, and Forging a Post-Cold War Order! - Bazian, Hatem (Religions, 2018)
Islamophobia, as a problem, is often argued to be a rational choice by the stereotypical media coverage of Islam and Muslims, even though it points to the symptom rather than the root cause. Islamophobia reemerges in public discourses and part of state policies in the post-Cold War period and builds upon latent Islamophobia that is sustained in the long history of Orientalist and stereotypical representation of Arabs, Muslims, and Islam itself. The book What is Islamophobia? Racism, Social Movements and the State, edited by Narzanin Massoumi, Tom Mills, and David Miller offers a unique contribution to how best to define and locate the problem of demonizing Islam and Muslims in the contemporary period. The three scholars provide a more critical and structural approach to the subject by offering what they call the five pillars of Islamophobia, which are the following: (1) the institutions and machinery of the state; (2) the far-right, incorporating the counter-jihad movement; (3) the neoconservative movement; (4) the transnational Zionist movement; and (5) the assorted liberal groupings including the pro-war left and the new atheist movement. The UK-based research group correctly situates Islamophobia within existing power structures and examines the forces that consciously produce anti-Muslim discourses, the Islamophobia industry, within a broad political agenda rather than the singular focus on the media. Islamophobia emerges from the Clash of Civilizations ideological warriors and not merely as a problem of media stereotyping, representation, and over-emphasis on the Muslim subject. In this article, I maintain that Islamophobia is an ideological construct that emerges in the post-Cold War era with the intent to rally the Western world and the American society at a moment of perceived fragmentation after the collapse of the Soviet Union in a vastly and rapidly changing world system. Islamophobia, or the threat of Islam, is the ingredient, as postulated in Huntington's Clash of Civilizations thesis that is needed to affirm the Western self-identify after the end of the Cold War and a lack of a singular threat or purpose through which to define, unify, and claim the future for the West. Thus, Islamophobia is the post-Cold War ideology to bring about a renewed purpose and crafting of the Western and American self.